Sustainable Architecture - from Principles to the Development Strategy - Jurayevich, Akhmedov Zokirjon (European Journal of Life Safety and Stability (2660-9630), 2022)
The article considers the concept of sustainability in the work of modern architects and urban planners, engineers and technologists. The detailed content of the principles makes it possible to apply them in research, design and experimental, scientific and educational activities. Approaches to the formation of a sustainable architecture development strategy are outlined.